Diagnostic Performance of Automated Breast Ultrasound in Differentiating Benign and Malignant Breast Masses in Asymptomatic Women: A Comparison Study With Handheld Ultrasound. (25th March 2019) - Niu, Lin; Bao, Lingyun; Zhu, Luoqian; Tan, Yanjuan; Xu, Xiaojing; Shan, Yanna; Liu, Jian; Zhu, Qingqing; Jiang, Chenxiang; Shen, Yingzhao
Abstract : Objectives: Our aim was to investigate the diagnostic potential of an automated breast ultrasound (ABUS) system in differentiating benign and malignant breast masses compared with handheld ultrasound (HHUS). Methods: Women were randomly and proportionally selected from outpatients and underwent both HHUS and ABUS examinations. Masses with final American College of Radiology Breast Imaging Reporting and Data System categories 2 and 3 were considered benign. Masses with final Breast Imaging Reporting and Data System categories 4 and 5 were considered malignant. The diagnosis was confirmed by pathologic results or at least a 1‐year follow‐up. Automated breast US and HHUS were compared on the basis of their sensitivity, specificity, positive predictive value, negative predictive value, and accuracy. Diagnostic consistency and areas under the receiver operating characteristic curves were analyzed. The maximum diameters of masses were compared among HHUS, ABUS, and pathologic results. Results: A total of 599 masses in 398 women were confirmed by pathologic results or at least a 1‐year follow‐up; 103 of 599 masses were malignant, and 496 were benign. There were no significant differences between ABUS and HHUS in terms of diagnostic accuracy (80.1% versus 80.6%), specificity (77.62% versus 80.24%), positive predictive value (46.12% versus 46.46%), and negative predictive value (97.96% versus 95.67%). There were significant differences in sensitivity (92.23% versus 82.52%; P < .01) and areas under the curve (0.85 versus 0.81; P < .05) between ABUS and HHUS. The correlation of the maximum diameter was slightly higher between ABUS and pathologic results ( r = 0.885) than between HHUS and pathologic results ( r = 0.855), but the difference was not significant ( P > .05). Conclusions: Automated breast US is better than HHUS in differentiating benign and malignant breast masses, especially with respect to specificity.